Globalisasi Media dan Transformasi Politik Internasional - Rianto, Puji (Jurnal ILMU KOMUNIKASI, 2008)
Abstract: Globalization affects almost everything, moreover international politics. In this respect, media that have transnational orientation, as serious patrons of globalization, keep transforming international politics in three dimensions which are from power politics to image politics, international politics mediation and the widespread utilization of media as propaganda.